Dynamic Hybrid Flagellar Motors—Fuel Switch and More - Thormann, Kai M. (Frontiers in Microbiology, 2022)
Flagellar motors are intricate rotating nanomachines that are powered by transmembrane ion gradients. The stator complexes are the powerhouses of the flagellar motor: They convert a transmembrane ion gradient, mainly of H+ or Na+, into rotation of the helical flagellar filament. They are thus essential for motor function. The number of stators synchronously engaged in the motor is surprisingly dynamic and depends on the load and the environmental concentration of the corresponding coupling ion. Thus, the stator-rotor interactions determine an important part of the properties of the motor. Numerous bacteria have been identified as possessing more than one set of stators, and some species have been demonstrated to use these different stators in various configurations to modify motor functions by dynamic in-flight swapping. Here we review knowledge of the properties, the functions, and the evolution of these hybrid motors and discuss questions that remain unsolved.